A emancipação do Mojuí dos Campos (PA) e as transformações socioespaciais - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The investigation aimed to analyse the sociospatial transformations from the municipal emancipation of Mojuí dos Campos, western Pará, and how the population was impacted by these changes. The first chapter presents notions of geographical space and territory using the concepts under the perspective of political power and the role of the Citizen. In the second chapter we discuss the processo of emancipation of Mojuí offering a brief historical approach of the village until the emancipation. The third one is about the municipality after the emancipation, its social and spatial transformations and the impacts in the population. Finally we put some answers for the questions that led to this research.
Keywords: Emancipação municipal; Mojuí dos Campos.; Transformações; Socioespaciais; CNPQ:: CIÊNCIAS HUMANAS